Winning with data : CRM and analytics for the business of sports - Green, Fiona, ....- (London : Routledge, 2019)
For many years, sports rights owners have had an 'if you build it, they will come' attitude, suggesting they take their fans for granted. Combined with advances in broadcasting quality, digital marketing, and social media, this has resulted in diminishing attendances and participation levels. The use of CRM (Customer Relationship Management), BI (Business Intelligence) and Data Analytics has therefore become integral to doing business in sports, emulating the approach used by brands such as Amazon, Netflix, and Spotify. Technology has made the world a smaller place; clubs and teams can now connect with their fans anywhere in the world, allowing them to grow their marketplace, but they operate in an 'attention economy' where there's too much choice and engagement is key. This book sets out to share the processes and principles the sports industry uses to capitalise on the natural loyalty it creates. Case studies and commentary from around the world are used to demonstrate some of the practices implemented by the world's leading sports brands including clubs Arsenal and the San Antonio Spurs. the governing bodies of UEFA and Special Olympics International, and the MLS and NHL. With a focus on our unique challenges coupled with the opportunities the use of data creates, this book is essential reading for professionals within the sports industry.